Kingdom of the Netherlands-Curacao and Sint Maarten : 2018 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
Weak growth and underlying structural vulnerabilities persist in both Curacao and Sint Maarten. Worsened macroeconomic conditions-reflecting the spillovers from one of Curacao's largest trading partners and the devastation from Hurricanes Irma and Maria in Sint Maarten-make the need for policy adjustment and structural reforms aimed at ensuring fiscal sustainability, enhancing competitiveness, strengthening investor confidence, and developing capacity more urgent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet